Comparative study on the effect of adding two transition-metal-substituted polyoxometalates on the mechanical properties of the (Bi, Pb)-2223 superconducting phase. (April 2021) - El Ghouch, Nour; Al-Oweini, Rami; Habanjar, Khulud; Awad, R
Abstract: This comparative study sheds light on the optimum addition x of K5 [SiFe(OH2 )W11 O39 ]·14H2 O (FeSiW11 ) and K6 [(H2 O)MnSiW11 O39 ]·21H2 O (MnSiW11 ) ( x = 0.02, 0.04, 0.08, 0.12, 0.16 and 0.20 wt%) nanoparticles to produce the desired mechanical characteristics of the (Bi, Pb)-2223 superconducting phase using a Vickers microhardness ( H V ) tester. H V measurement was performed at room temperature for different applied loads (0.245–9.8 N) and times (10–60 s). From the H V measurements, all the prepared samples had a normal 'indentation size effect' behaviour. It was found that 0.04 wt% FeSiW11 nanoparticles and 0.08 wt% MnSiW11 nanoparticles were the optimal addition to increase the microhardness of the (Bi, Pb)-2223 phase. Accordingly, other mechanical parameters for potential applications, such as the elastic modulus, yield strength and fracture toughness of the samples studied, were extracted from H V as a function of nanoparticle addition. The measured H V data were theoretically analysed with use of different models. The modified proportional sample resistance model was identified as the best theoretical model to describe the true H V values for both phases. Indentation creep analysis was also performed using time-dependent microhardness to indicate the enhancement of new cavity formation in the measured samples. Highlights: The Vickers microhardness of new polyoxometalate–(Bi, Pb)-2223 composites was studied. The Vickers microhardness was increased by addition of both polyoxometalates. All measured samples exhibit normal indentation size effect behaviour. The experimental data are well fitted by the modified proportional sample resistance model. Enhancement of new cavity formation was implied from indentation creep analysis.